Asymmetric Synthesis of Both Enantiomers of a δ-Lactone Analogue of Muricatacin - Doran, Robert; Guiry, Patrick J. (Synthesis, 2014)
The asymmetric synthesis of both enantiomers of the δ-lactone analogue of the antitumoral natural product γ-lactone muricatacin has been carried out. Initial attempts to also synthesize the natural product proved unsuccessful due to the poor reactivity of the Grignard reagent derived from 2-(bromomethyl)-1,3-dioxolane. The designed synthetic route enabled us to increase the ring size to generate the δ-lactone analogue employing Sharpless asymmetric epoxidation and ZrCl4-catalyzed intramolecular acetalization as the key steps.
Keywords: muricatacin; asymmetric synthesis; zirconium tetrachloride; natural product analogues; δ-lactone